Condutividade térmica de compostos XTe (X=Cd,Pb) nanoestruturados a partir de simulações computacionais - Lorenset, Guilherme Aluizio Steffens (2018)
In this work we study the thermal conductivity coefficient κ of bidimensional nanostructured systems of cadmium telluride (CdTe) and lead telluride (PbTe). At room temperature and bulk phase, these compounds present values of κ coefficient lower than the silicon bulk. Low values of lattice thermal conductivity are a requirement to present a high thermoelectric efficiency, that is quantified by the figure of merit, which is inversely proportional to the system thermal conductivity. In contrast, materials with high values of thermal conductivity are targeted in the electronics industry, mainly like heat sinks. When compared to bulk, the nanostructures generally present a lower thermal conductivity value and thereby they have a potential to reach higher thermoelectric efficiency. Hence, the knowledge of this coefficient, as well as its behavior, is of extreme importance for the correct applicability of the material. In thiw work, two different computational simulations approaches are used to computed the thermal conductivity. Initially, molecular dynamics simulations using the LAMMPS code and the Green-Kubo method are used. This method is widely used in the literature by correctly describing the κ value of bulk and nanostructured systems. The interaction potentials to simulate these systems are found in the literature. At 300 K we found a value of 2, 81 W/mK to the PbTe bulk, in agreement with the literature. The nanostructured systems of PbTe studied are composed of bidimensional nanosheets with thickness ranging from one layer to three layers of atoms. For one atom thickness of PbTe nanosheet, we found a lattice thermal conductivity about 50% lower than the bulk PbTe, but with the increase of the number of layers in the system, the thermal conductivity coefficient follow the bulk result. The CdTe bulk present far values from the experimental and theoretical studies, found by other methodologies This can be related with the absence of correct parametrization to this property and partial charges in the interatomic potential used. Due these results, first principles simulations with DFT are performed to study the systems. At room temperature, is calculated to the PbTe crystal a value of 2, 06 W/mK, while to the monolayer and bilayer are found values of 0, 44 and 0, 53 W/mK respectively. To CdTe systems we got values around 3, 37 and 0, 15 W/mK, to the bulk and nanosheet respectively. Thereby, we have that the bidimensional nanostructures studied have significant reduction in their thermal conductivity, suggesting potential thermoelectric applications.